TEORI BELAJAR HUMANISTIK DAN IMPLIKASINYA DALAM PEMBELAJARAN - Etmi Hardi; Azwar Ananda; Mukhaiyar Mukhaiyar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Learning is not only memorizing and not remembering, but learning is a process characterized by changes in students. Changes because of the learning process can be demonstrated in various forms, such as changes in knowledge, attitudes, skills, skills, abilities, reaction power and receptivity. So, learning is an active process, a process of reacting to all the situations that exist in the learner. Learning is a process that is directed towards a goal, the process of doing through the situation that exists in the learner. Frandsen said that what drives a person to learn is partly due to curiosity, creative nature, and the desire to correct past failures (Darsono, 2001). Based on humanistic learning theory the purpose of learning is to humanize a human being. Learning activities are considered successful if the learner understands his environment and himself. The student in the learning process must strive so that he is slowly able to achieve self-actualization well. Humanistic learning theory seeks to understand learning behaviour from the point of view of the learner (student), not from the one who provides learning (the teacher). The task of the teacher is only to help the student in the process of self-development, to better recognize himself as a human being, to actualize all the potential that exists in him. The presentation above shows how important it is to describe and study humanistic learning theory and its implications in learning during educational failures in Indonesia which are more concerned and only make cognitive aspects the biggest reference in measuring the quality of education. This paper tries to explain humanistic learning theory, its application, and implications in learning.